GOVERNMENT’S ROLE IN DEVELOPING SUSTAINABLE TOURISM AT SANGIHE ISLAND REGENCY - Steven Y. Kawatak; Machiko Nugraha Indriyanto; Yolanda M.K.H. Jangkobus (Jurnal Ilmiah Hospitality, 2020)
Tourism is a leading sector and source of income for many local governments, including the government of Sangihe Islands Regency. Sustainable tourism development has been considered as a major factor in maintaining the environmental integrity, as well as social and economic equality of a region’s tourist attractions. This study uses qualitative research, where the data collection was carried out by observation, documentation and interviews with the stakeholders of tourism in the regency, in particular the local Cultural and Tourism Office. Moreover, in this research, the potentials of the Sangihe Islands Regency were identified and categorized into three, namely Cultural, Natural and Maritime, and Nature Reserve tourism potentials. The local government’s policies to improve and develop its sustainable tourism are then divided into four main aspects, which are the development of tourist destinations, tourism marketing, tourism industry, and tourism institutions. Lastly, the strengths, weaknesses, opportunities, and threats are identified in order to develop strategies that would support and improve the development of sustainable tourism in Sangihe Islands Regency.